Breastfeeding grief after chest masculinisation mastectomy and detransition: A case report with lessons about unanticipated harm - Gribble, Karleen D.; Bewley, Susan; Dahlen, Hannah G. (Frontiers in Global Women's Health, 2023)
An increasing number of young females are undergoing chest masculinsation mastectomy to affirm a gender identity and/or to relieve gender dysphoria. Some desist in their transgender identification and/or become reconciled with their sex, and then revert (or detransition). To the best of our knowledge, this report presents the first published case of a woman who had chest masculinisation surgery to affirm a gender identity as a trans man, but who later detransitioned, became pregnant and grieved her inability to breastfeed. She described a lack of understanding by maternity health providers of her experience and the importance she placed on breastfeeding. Subsequent poor maternity care contributed to her distress. The absence of breast function as a consideration in transgender surgical literature is highlighted. That breastfeeding is missing in counselling and consent guidelines for chest masculinisation mastectomy is also described as is the poor quality of existing research on detransition rates and benefit or otherwise of chest masculinising mastectomy. Recommendations are made for improving maternity care for detransitioned women1. Increasing numbers of chest masculinsation mastectomies will likely be followed by more new mothers without functioning breasts who will require honest, knowledgeable, and compassionate support.